The Imbalance of Circulating Follicular T Helper Cell Subsets in Primary Sjögren’s Syndrome Associates With Serological Alterations and Abnormal B-Cell Distribution - Szabó, Krisztina; Jámbor, Ilona; Szántó, Antónia; Horváth, Ildikó Fanny; Tarr, Tünde; Nakken, Britt; Szodoray, Peter; Papp, Gábor (Frontiers in Immunology, 2021)
Since B-cell hyperactivity and pathologic antibody response are key features in the immunopathogenesis of primary Sjögren’s syndrome (pSS), the role of follicular T helper (TFH) cells as efficient helpers in the survival and differentiation of B cells has been emerged. Our aim was to investigate whether a change in the balance of circulating (c)TFH subsets and follicular regulatory T (TFR) cells could affect the distribution of B cells in pSS. Peripheral blood of 38 pSS patients and 27 healthy controls was assessed for the frequencies of cTFH cell subsets, TFR cells and certain B cell subpopulations by multicolor flow cytometry. Serological parameters, including anti-SSA, anti-SSB autoantibodies, immunoglobulin and immune complex titers were determined as part of the routine diagnostic evaluation. Patients with pSS showed a significant increase in activated cTFH cell proportions, which was associated with serological results. Frequencies of cTFH subsets were unchanged in pSS patients compared to healthy controls. The percentages and number of cTFR cells exhibited a significant increase in autoantibody positive patients compared to patients with seronegative pSS. The proportions of transitional and naïve B cells were significantly increased, whereas subsets of memory B cells were significantly decreased and correlated with autoantibody production. Functional analysis revealed that the simultaneous blockade of cTFH and B cell interaction with anti-IL-21 and anti-CD40 antibodies decreased the production of IgM and IgG. Imbalance in TFH subsets and TFR cells indicates an ongoing over-activated humoral immune response, which contributes to the characteristic serological manifestations and the pathogenesis of pSS.